Globalism and anti-globalism in modern Orthodox discourse - Gridchin, Anton V. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
The article examines the concepts of «globalism», «antiglobalism», «alterglobalism» and their reflection in modern Christianity. The views on the concept of ethnic identity in Christian theology and canon law are considered. The historical retrospective of globalist tendencies in Christianity is analysed. A distinction is made between Christian confessions based on their assessments of the theory and practice of globalisation. The concept of «ethnophyletism» is analysed as a manifestation of globalist ideology in modern Orthodoxy. The anti-globalist discourse is characterised within the framework of traditionalist and fundamentalist trends in modern Orthodoxy. The concept of the Russian world is analysed from the point of view of the ideology of alternative globalism.
Keywords: globalism; antiglobalism; alterglobalism; fundamentalism; traditionalism; herodianism; zealotism; civilisational approach; Russian world